2004
DOI: 10.1002/ijc.20329
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles in breast tumors regarding the presence or absence of estrogen and progesterone receptors

Abstract: Estrogen acts via its receptor (ER) to stimulate cell growth and differentiation in the mammary gland. ER and progesterone receptor (PR), which is regulated by estrogen via ER, have been used as prognostic markers in clinical management of breast cancer patients. Patients with ER ؊ breast tumors have a poorer prognosis than patients with ER ؉ tumors. The aim of the present study was the identification of tumor-associated genes differentially expressed in breast tumors regarding the presence or absence of ER an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
3
18
0
3
Order By: Relevance
“…The majority of breast cancers stain positively for both PGR and estrogen receptor; receptor positivity is predictive of response to tamoxifen and overall survival. More recently, microarray studies have found PGRnegative tissue to have high levels of transcripts of genes associated with cell proliferation (15).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of breast cancers stain positively for both PGR and estrogen receptor; receptor positivity is predictive of response to tamoxifen and overall survival. More recently, microarray studies have found PGRnegative tissue to have high levels of transcripts of genes associated with cell proliferation (15).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we employed an integrated computer-assisted and manual search to identify EREs in the promoter region of a set of candidate ER target genes previously identified as being differentially expressed in primary breast tumors based on their estrogen and progesterone status (21). Using this approach, we characterized the promoter region of 83 genes for their potential to be regulated by ER.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we performed an integrated computational and manual search to identify potential ER binding sites in the promoter region of 83 genes previously identified as being differentially expressed in primary breast tumors based on the presence of estrogen and progesterone receptors (21). We identified a subgroup of genes arranged in a head-to-head orientation and separated by a small intergenic region that could be classified as bidirectional promoters.…”
mentioning
confidence: 99%
“…Patients with ER ( À ) breast tumors have a poorer prognosis than patients with ER ( þ ) tumors [60].The estrogen receptor alpha (ESR1) is a mediator of estrogen response in the breast. The most studied variants in this gene are the PvuII and XbaI polymorphisms, but conversely, they do not play a role in breast cancer risk in Caucasian postmenopausal women [61].…”
Section: Proto-oncogenesmentioning
confidence: 99%